Interleukin‐4 administration improves muscle function, adult myogenesis, and lifespan of colon carcinoma‐bearing mice. Issue 3 (27th February 2020) - Costamagna, Domiziana; Duelen, Robin; Penna, Fabio; Neumann, Detlef; Costelli, Paola; Sampaolesi, Maurilio
Abstract: Background: Anorexia, body wasting, inflammation, muscle, and adipose tissue loss are hallmarks of cancer cachexia, a syndrome that affects the majority of cancer patients, impairing their ability to endure chemotherapeutic therapies and reducing their lifespan. In the last 10 years, alterations of protein turnover and impairment of adult myogenesis have been proposed as major contributing factors. Methods: Muscle stem cells, including satellite cells, mesoangioblasts, and fibroadipogenic progenitors, were isolated and characterized from C26 colon carcinoma‐bearing (C26) mice. Circulating levels of interleukin‐4/13 (IL4/IL13) were analysed by ELISA, and the effects of IL4 on muscle mass and function, protein synthesis, muscle regeneration, and myogenic progenitor cell number were analysed at both functional (treadmill and grip test) and molecular levels (qRT–PCR, immunofluorescence analysis, surface sensing of translation, and western blot). The Kaplan–Meier test was used to analyse the survival curve of IL4‐treated and IL4‐untreated C26 mice. Results: The administration of IL4 to C26 mice rescued muscle mass by increasing protein synthesis. The IL4 treatment improved performances and prolonged survival of C26 mice. IL4 administration re‐established both number and function of satellite cells and fibroadipogenic progenitors without affecting mesoangioblasts in C26 mice, rescuing myogenesis. Upon IL4 treatment, a high number of cytotoxic lymphocytes and type II macrophages were observed with a subsequent increase in necrotic areas of C26 tumours. Conclusions: The results here presented shed new light on IL4 signalling during muscle wasting and early stages of muscle regeneration that explain the beneficial effect observed in IL4‐treated C26 mice. These findings might aid to develop therapeutic approaches to improve mobility and quality of life in cachectic patients.